TELAAH USHUL AL-TAFSIR TERHADAP KONSEP ABROGASI (NASKH) DALAM TAFSIR KLASIK - Egy Bayu Adhani; Zulfikar Hafizh; Padli Johari; Aksir Amwali; Anwar Sidik (AT-TAISIR: Journal of Indonesian Tafsir Studies, 2025)
This research aims to gain a deeper understanding of how classical Qur’anic exegetes sch as imam al-Thabari, al-Qurthubi, and al-Suyuti, who are scholars of tafsir from various periods in Islamic history, interpret and apply the concept of abrogation (naskh) in the context of the verses of the Qur’an. The researcher willexplore various approaches and methodologies used by classical mufassir in explaining the phenomeon of naskh, as well as how they interpret verses that are considered to have been abrogated or replaced by other verses. The methodology employed in this research is qualitative analysis with an indepth literature study approach. The researcher examine various classical tafsir works produced by prominent mufassir, as well as analyze the historical and cultural contexts in which these tafsir were written. The results of the research indicate that there is significant variation in the understanding and application of the concept of naskh among classical mufassir. Some mufassir emphasize historical and kontextual aspects, striving to understand the social and cultural background of the verses that are considered abrogated, thus providing a deeper explanation of the legal changes within the Qur’an. The research recommends further in depth studies on the influence of social and cultural contexts on the interpretation of naskh. Understanding these factors is essentialfor obtaining a more comprehensive perspective on the application of naskh in various circumstances and contributes to enriching the muslim understanding of the Qur’an and its application in contemporary life.